Dual roles for a tick protein disulfide isomerase during the life cycle of the Lyme disease agent - Xiaotian Tang; Yingjun Cui; Ushuu Namarra; Xiuqi Tian; Freddie Rivas-Giorgi; Erol Fikrig (mBio, 2024)
ABSTRACT The protein disulfide isomerase (PDI) family is a group of enzymes that have thiol-disulfide oxidoreductase, disulfide isomerase, and redox-dependent chaperone activities. PDIs facilitate diverse infections in mammalian hosts by directly binding to pathogens, immunomodulation, or enabling microbial invasion of host cells. PDI homologs within pathogens are also potential virulence factors. However, whether PDIs within blood-feeding ticks influence microbial infection remains unknown. In this study, we investigated the role of Ixodes scapularis PDIs, on the Lyme disease agent, Borrelia burgdorferi. I. scapularis has five PDIs (IsPDIs), and IsPDIA6 gene expression is reduced upon B. burgdorferi infection in the tick. IsPDIA6-mediated trypsin inhibitor gene expression contributes to B. burgdorferi colonization within the tick midgut. IsPDIA6 is also secreted into the host during tick feeding, alters cytokine/chemokine expression at the tick bite site, and influences the initial stage of bacterial infection in mice. These data demonstrate that a PDI from a blood-feeding vector plays a role in the life cycle of an extracellular pathogen.IMPORTANCEVector-borne diseases are a leading cause of death and illness worldwide, and more than 80% of the global population live in areas at risk from at least one major vector-borne disease. In this study, we demonstrate a dual role of a specific Ixodes tick protein disulfide isomerase (PDI) in inhibiting the ability of the Lyme disease agent to colonize ticks and also in enhancing the initial stage of spirochete infection of mice. This study represents a novel conceptual advancement that a PDI from a blood-feeding vector plays important roles in the life cycle of an extracellular pathogen.